(untitled) (Vietnam Journal of Community Medicine, 2026)
ABSTRACT Objectives: To evaluate the treatment outcomes of concurrent chemoradiotherapy for stage III non-small cell lung cancer (NSCLC) and some prognostic factors. Materials and Methods: A retrospective longitudinal study was conducted on 119 patients with stage III NSCLC who received concurrent chemoradiotherapy at Nghe An Oncology Hospital from March 2019 to December 2022. Results: The mean age was 59.3 ± 9 years, with a male-to-female ratio of 5:1; stage IIIB was most prevalent (50.4%). The overall response rate was 98.3% (complete response 17.6%). Median progression-free survival (PFS) was 12 months and median overall survival (OS) was 26 months, with a 5-year survival rate of 31.5%. A tumor size of ≤ 5 cm prolonged median PFS (16 months, p = 0.010) and OS (39 months, p = 0.041). Stage IIIA showed higher median PFS and OS (21 and 48 months) than stage IIIB and IIIC. Adverse events were predominantly grade 1–2; grade 3–4 toxicities were mainly leukopenia and thrombocytopenia. Conclusion: Concurrent chemoradiotherapy in patients with stage III NSCLC yields favorable long-term survival. Small tumor size (≤ 5 cm) and early disease stage (IIIA) are prognostic factors that prolong survival.